Plant Morphoecological Traits, Grass-Weed Interactions and Water Use Efficiencies of Grasses Used for Restoration of African Rangelands - Mganga, Kevin Z.; Kaindi, Eric; Ndathi, Aphaxard J. N.; Bosma, Luwieke; Kioko, Theophilus; Kadenyi, Nancy; Musyoki, Gilbert K.; Wambua, Stephen; van Steenbergen, Frank; Musimba, Nashon K. R. (Frontiers in Ecology and Evolution, 2021)
Degradation characterized by depleted vegetation cover is a serious environmental problem in African rangelands. It poses a serious threat to millions of pastoralists and agropastoralists who depend on livestock as a source of livelihood. Consequently, there has been a growing global interest to consolidate efforts to restore degraded ecosystems. For example, the UN decade of Ecosystem Restoration initiative aims at uniting the world behind a common goal of preventing, halting and reversing the degradation of ecosystems. Grass reseeding using native perennial species has been identified as one of the practical ecological strategies for restoring degraded African rangelands, enhancing vegetation cover and forage production. Knowledge of the multifaceted performance of African rangeland grasses in terms of morphoecological traits, interaction with weeds and water use efficiencies is however largely limited and often elusive. Perennial grasses indigenous to African rangelands Cenchrus ciliaris L. (African foxtail grass), Enteropogon macrostachyus (Hochst. Ex A. Rich.) Monro ex Benth. (Bush rye grass) and Eragrostis superba Peyr. (Maasai love grass), were established in an African semi-arid rangeland under natural conditions to fill this knowledge gap. Morphoecological plant traits: aboveground biomass (shoot, leaf and stem) production, plant densities, basal cover, tiller densities and plant height were measured nine months after establishment. Interaction between the target grass species and weeds and water use efficiencies (WUE) were also determined. Enteropogon macrostachyus displayed significantly higher values for plant densities, tiller densities and basal cover, indices commonly used to estimate the potential of grasses for ecological restoration. Eragrostis superba produced the highest shoot biomass and water use efficiencies. This is attributed to its higher leafy biomass fraction. Higher aboveground biomass production of E. superba demonstrate its suitability for enhancing rangeland productivity. Cenchrus ciliaris suppressed the weeds. This is linked to its aggressive and allelopathic nature. In conclusion, the three perennial grasses displayed distinct morphoecological traits. In order to achieve successful seed-based restoration of degraded African rangelands using native perennial grasses, careful selection species to maximize on their unique traits is recommended. Ultimately, this selection process should match the desired restoration outcomes and subsequent use of the rangeland.